2019
DOI: 10.21608/msnj.2019.187791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program about Infection Control Precautions for Nurses in Pediatric Hemodialysis Units

Abstract: Background: Hemodialysis places children at high risk for infection because of patient comorbidities and numerous human, environmental, and procedural factors. The aim of this study was to evaluate the effect of the educational program on the nurse's knowledge and their practices about infection control measures in hemodialysis units. Research design: Pre /post quasi experimental design was used in this study. Sample: A convenient sample of all nurses in hemodialysis units, Setting: the study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The present study agreed with another study [22] in Minia/Egypt pre/post-quasi-experimental design in pediatric hemodialysis units at Minia University and Minia General Hospitals and showed another point which pointed out that education and educational programs will affect wearing gloves, administration of injectable drugs, and total nurses' practices against infectious control (p = 0.001). Finally, a study in the Karongi district in Rwanda showed a significant association between the education level (high school = 0.061 and university = 0.035) and the practices of HCPs [13].…”
Section: Discussionsupporting
confidence: 91%
“…The present study agreed with another study [22] in Minia/Egypt pre/post-quasi-experimental design in pediatric hemodialysis units at Minia University and Minia General Hospitals and showed another point which pointed out that education and educational programs will affect wearing gloves, administration of injectable drugs, and total nurses' practices against infectious control (p = 0.001). Finally, a study in the Karongi district in Rwanda showed a significant association between the education level (high school = 0.061 and university = 0.035) and the practices of HCPs [13].…”
Section: Discussionsupporting
confidence: 91%
“…Correspond with study was conducted in Minia that was study effect of educational program about infection control precautions for nurses in pediatric hemodialysis units while the participants were 36 nurses show the results no significant in pre-test pvalue = 0.9 ,post-1p-value = 0.3, and post-test 2 p-value = 0.3. (13) Recommendation:…”
Section: Discussionmentioning
confidence: 99%